Revisiting the dynamical masses of the transiting planets in the young AU Mic system: potential AU Mic b inflation at ~20 Myr - Mallorquín, Manuel; Béjar, V. J. S.; Lodieu, N.; Zapatero Osorio, Maria Rosa; Yu, H.; Suárez Mascareño, Alejandro; Damasso, Mario; Sanz-Forcada, J.; Ribas, Ignasi; Reiners, Ansgar; Quirrenbach, Andreas; Amado, Pedro José; et al. (Astronomy and astrophysics, 2024)
Context. Understanding planet formation is important in the context of the origin of planetary systems in general and of the Solar System in particular, as well as to predict the likelihood of finding Jupiter, Neptune, and Earth analogues around other stars. Aims. We aim to precisely determine the radii and dynamical masses of transiting planets orbiting the young M star AU Mic using public photometric and spectroscopic datasets. Methods. We performed a joint fit analysis of the TESS and CHEOPS light curves and more than 400 high-resolution spectra collected with several telescopes and instruments. We characterise the stellar activity and physical properties (radius, mass, density) of the transiting planets in the young AU Mic system through joint transit and radial velocity fits with Gaussian processes.
Online verfügbar: 10. September 2024
Gesehen am 11.03.2025